Replicated biopolymer pattern on PLLA-Ag basis with an excellent antibacterial response - Frýdlová, Bára; Fajstavr, Dominik; Slepičková Kasálková, Nikola; Rimpelová, Silvie; Svobodová Pavlíčková, Vladimíra; Švorčík, Václav; Slepička, Petr (Heliyon, 2023)
The design of functional micro or nanostructured surfaces is undergoing extensive research for their intriguing multifunctional properties and for large variety of potential applications in biomedical field (tissue engineering or cell adhesion), electronics, optics or microfluidics. Such nanosized topographies can be easily fabricated by various lithography techniques and can be also further reinforced by synergic effect by combining aforementioned structures along materials with already outstanding antibacterial properties. In this work we fabricated novel micro/nanostructured substrates using soft lithography replication method and subsequent thermal nanoimprint lithography method, creating nanostructured films based on poly (l-lactic acid) (PLLA) fortified by thin silver films deposited by PVD. Main nanoscale patterns were fabricated by replicating surface patterns of optical discs (CDs and DVDs), which proved to be easy, fast and inexpensive method for creating relatively large area patterned surfaces. Their antimicrobial activity was examined in vitro against the bacteria Escherichia coli and Staphylococcus epidermidis strains. The results demonstrated that nanopatterned films actually improved the conditions for bacterial growth compared to pristine PLLA films, the novelty is based on formation of Ag nanoparticles on the surface/and in bulk, while silver nanoparticle enhanced and nanopatterned films exhibited excellent antibacterial activity against both bacterial strains, with circa 80 % efficacy in 4 h and complete bactericidal effect in span of 24 h.
Keywords: Antibacterial properties; Nanopattern; Silver nanoclusters; poly(l-lactic acid); Replication; Nanostructures; PDMS; Soft-lithography; Hot-embossing; Nano-lithography; Organic coating